2019
DOI: 10.1051/0004-6361/201732485
|View full text |Cite
|
Sign up to set email alerts
|

Massive galaxies on the road to quenching: ALMA observations of powerful high redshift radio galaxies

Abstract: We present 0 . 3 (band 6) and 1 . 5 (band 3) ALMA observations of the (sub)millimeter dust continuum emission for 25 radio galaxies at 1 < z < 5.2. Our survey reaches a rms flux density of ∼50 µJy in band 6 (200-250 GHz) and ∼20 µJy in band 3 (100-130 GHz). This is an order of magnitude deeper than single-dish 850 µm observations, and reaches fluxes where synchrotron and thermal dust emission are expected to be of the same order of magnitude. Combining our sensitive ALMA observations with low-resolution radio … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
76
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 55 publications
(86 citation statements)
references
References 175 publications
(255 reference statements)
8
76
2
Order By: Relevance
“…This observation implies that dust has a negligible contribution to the SED at the host galaxy. Moreover, Falkendal et al (2019) have shown that the star-formation rate (SFR) in Yggdrasil, is low in comparison to that which is detected in the companion sources, collectively.…”
Section: Agn Photoionisation Of the Absorbersmentioning
confidence: 98%
See 1 more Smart Citation
“…This observation implies that dust has a negligible contribution to the SED at the host galaxy. Moreover, Falkendal et al (2019) have shown that the star-formation rate (SFR) in Yggdrasil, is low in comparison to that which is detected in the companion sources, collectively.…”
Section: Agn Photoionisation Of the Absorbersmentioning
confidence: 98%
“…Stellar photoionisation is a possibility as well. The starformation rate (SFR) in Yggdrasil, however, is SFR=41 M yr −1 (Falkendal et al 2019) and may be insufficient in producing the star-burst activity that would ionise the absorbers. Another pos-Article number, page 14 of 21 S. Kolwa et al: MUSE unravels the ionisation and origin of metal enriched absorbers in the gas halo of a z = 2.92 radio galaxy Fig 14(d) which is a spectrum extracted from an aperture centred at the HSBR over a radius of R = 0.6 ).…”
Section: Musementioning
confidence: 99%
“…The UV and optical continuum slopes are measured from the observed spectrum. The quoted L IR refers to that attributed to star formation only, excluding any AGN contribution (Falkendal et al 2019).…”
Section: Vlt/x-shooter Observationsmentioning
confidence: 99%
“…2, corresponding to moderate spectral resolutions of λ/∆λ ∼ 3200, 5000, and 4300, which were sampled at 8.9, 10.3, and 22.6 pixels per FWHM, respectively. The slit was broad enough to cover both the host galaxy and the radio lobe of PKS 0529-549 (corresponding to the W and E components as presented in Broderick et al 2007;Falkendal et al 2019). The integration times per exposure in the UVB, VIS, and NIR arms were 1800, 900, 600 s, respectively.…”
Section: Vlt/x-shooter Observationsmentioning
confidence: 99%
See 1 more Smart Citation